Surgery 101 Podcast: Episodes 41-50 - Jonathan White; Daniel Birch; Marcia Clark; Chris de Gara; Shahzeer Karmali; Ruth McGaffigan; Dereck Mok; Dan Schiller (Association of American Medical Colleges, 2011)
Abstract This resource is a series of podcasts intended to serve as brief introductions to and reviews of surgical topics for medical students. The aim was to cover a single topic in 15-20 minutes so that learners could quickly grasp the basic concepts relating to common surgical problems. Learning objectives are provided for each episode; episodes are divided into chapters and conclude with several key points to summarize the topic. This module contains topics/episodes on enlarged lymph node, adult soft-tissue sarcoma, surgery for morbid obesity, minimally invasive surgery, orthopedic emergencies, hemorrhoids, damage-control surgery, enterocutaneous fistula, trauma in pregnancy, and surgical training. Surgery 101 has been produced since October 2008; it was created by Dr. Parveen Boora and Dr. Jonathan White and is currently produced by the Undergrad Surgery Mobile Podcasting Studio Team with the assistance of the members of the Surgery Department at the University of Alberta.